Implikasi Manajemen Laba Dan Leverage Terhadap Aplikasi Tax Avoidance - NURCAHYO DARMAWAN, ARI; LUCY KRISTIAN, ERIVINA (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
This research aims to determine and analyze the influence of company size, profitability, leverage, and earnings management on tax avoidance simultaneously and partially, as well as the influence of political connections as a moderating variable in mining companies listed on the Indonesia Stock Exchange (BEI). The population in this study are companies listed in the mining sector on the Indonesia Stock Exchange (BEI) for the period 2020–2021. The sample in this study uses a saturated sampling technique (census), so a population of 47 companies will be used as the total sample for 12 consecutive years., respectively, so that the total observations are 478 companies. The results of hypothesis testing prove that company size, profitability, leverage, and earnings management simultaneously have a significant effect on tax avoidance. Partially, company size has a positive and insignificant effect on tax avoidance; profitability and leverage have a significant positive effect on tax avoidance; and earnings management has a negative and insignificant effect on tax avoidance. Political connections are significant in moderating profitability through tax avoidance, and political connections are not significant in moderating company size, leverage, or earnings management through tax avoidance.